1999
DOI: 10.1111/j.1540-8159.1999.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of the Left Atrium Evaluated by Coronary Sinus Pacing in Patients with Atrial Fibrillation

Abstract: Repetitive atrial firing (RAF), marked fragmentation of atrial activity (FAA), and interatrial conduction delay (CD) have been shown to be electrophysiological features of the atrium in patients with atrial fibrillation (AF). Moreover, it has been observed that atrial extrastimuli are more likely to induce AF when delivered from the right atrial appendage (RAA) than from the distal coronary sinus (CSd). We examined the electrophysiological properties of the atrial muscle by CS and RAA stimulation in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…Those patients with induction of AF showed a larger dispersion of refractoriness due to a marked difference between ERP at the right atrium and those obtained along the CS. These findings are in accordance with other authors, who reported shorter ERP in the high right atrium when compared with distal CS in patients with AF [7,21]. This may be explained by a non-uniform distribution of vagal nerve endings, which seems to cause greater changes in refractory period in the RAA than in left atrium [22].…”
Section: Atrial Refractory Periodssupporting
confidence: 82%
See 1 more Smart Citation
“…Those patients with induction of AF showed a larger dispersion of refractoriness due to a marked difference between ERP at the right atrium and those obtained along the CS. These findings are in accordance with other authors, who reported shorter ERP in the high right atrium when compared with distal CS in patients with AF [7,21]. This may be explained by a non-uniform distribution of vagal nerve endings, which seems to cause greater changes in refractory period in the RAA than in left atrium [22].…”
Section: Atrial Refractory Periodssupporting
confidence: 82%
“…Therefore, it is not possible to compare ERP to the right atrium and pulmonary veins in this population. Nevertheless, in previous studies, the distal CS ERP was accepted as reflecting the ERP of the local left atrial tissue [21,33]. Finally, although the number of subjects included in the study allowed for the identification of significant differences in the dispersion of atrial refractoriness, the resulting sample was relatively small, representing only a subpopulation of patients with PAF and absent or minimal structural heart disease.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Our results differed from those of Ishimatsu, et al 3) who showed that the MCT from the HRA to the DCS during HRA pacing was significantly longer than that from the DCS to the HRA during DCS pacing in patients with or without paroxysmal AF. This discrepancy is not apparent but could be due to a different patient population.…”
Section: Discussioncontrasting
confidence: 57%
“…2,3) The incremental conduction delay at different atrial regions during HRA pacing has been shown to be significantly attenuated by "biatrial pacing" defined as pacing simultaneously from the HRA and the DCS. 2,4) The wavelength for circus movement in the heart has been defined as the distance traveled by the depolarization wave during the duration of the refractory period (wavelength=conduc-tion velocity X refractory period).…”
mentioning
confidence: 99%
“…Data on the harmful effect of CSp on RA function are rare, as most studies have focused on LA function and its beneficial electrical properties. 28 Only a few studies have assessed the RA function during CSp. Kutarski et al investigated the influence of CSp on signal-avaraged P-wave time domain parameters and demonstrated that in patients with interatrial conduction disturbances, CSp reduced LA late potentials, but at the same time failed to restore homogeneity of activation within the RA.…”
Section: Dąbrowska-kugacka a Et Almentioning
confidence: 99%